Taxonomical study of the euphorbiaceae family at the Yok Don national park, Dak Lak province - Hoa, Nguyen Thi; Kim Thanh, Nguyen Thi; Thin, Nguyen Nghia (Academia Journal of Biology, 2014)
During the time to study on Euphorbiaceae at the Yokdon national park, Daclac province, 27 species belonging to 16 genera, 14 tribes and 4 subfamilies have been analyzed and identified. Among them, 24 species had been fully indentified while the remainders were still unidentified and maybe new for the Vietnam flora. Phyllanthoideae is the most rich subfamily with 6 tribes, 8 genera and 15 species. Two richest tribes are Phyllantheae with 2 genera, 5 species and Glochideae with 2 genera, 4 species. The genera Euphorbia and Phyllanthus are the richest ones with 4 species for each. A classification system and an indentified key to species were also established.